2005
DOI: 10.1196/annals.1313.092
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Nature of Influenza Atherogenicity

Abstract: It has been observed during influenza epidemics and in a number of population and clinical trials that this prevalent viral infection was associated with increased death rates from cardiovascular diseases. The clinical and experimental data that may explain accelerated coronary atherosclerosis in influenza infection with implications involving autoimmune mechanisms are analyzed in this article. Both cellular and humoral autoimmune modes could be proposed to participate in the onset or progression of atheromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Another current hypothesis is that direct colonization of the vessel wall initiates local cell autoimmune reactions by activation of antigen-presenting cells. 17 …”
Section: Influenza Among Patients With Cvdmentioning
confidence: 99%
“…Another current hypothesis is that direct colonization of the vessel wall initiates local cell autoimmune reactions by activation of antigen-presenting cells. 17 …”
Section: Influenza Among Patients With Cvdmentioning
confidence: 99%
“…One current hypothesis is that the inflammatory response of the body to viral infection leads to production of autoantibodies to modified low-density lipoprotein, which causes the development and progression of atherosclerotic vascular injury. Another current hypothesis is that direct colonization of the vessel wall initiates local cell autoimmune reactions by activation of antigen-presenting cells (17).…”
Section: Influenza Among Patients With Cvdmentioning
confidence: 99%
“…Genetic studies can potentially address this issue using a Mendelian randomization approach. In support of these genetic association studies, inflammatory diseases have also been shown to strongly associate with cardiovascular diseases [19]. By contrast, a causal role for a cytokine upstream of CRP, interleukin (IL)-6 [15,16], was elegantly demonstrated by two independent research consortia [17 && ,18 && ].…”
Section: Inflammation and Atherosclerosismentioning
confidence: 99%